Predictors of Successful Urogenital Fistula Repair and Incidence of Urinary Problems Post Successful Fistula Repair - Tasnim, Nasira; Bangash, Kauser; Amin, Oreekha; Batool, Afshan; Javed, Nosheela (Nepal Journal of Obstetrics and Gynaecology, 2018)
Objective: Despite the successful fistula repair many patients may continue to complaint of persistence of symptoms in terms of frequency, urgency, urge incontinence and stress incontinence. To evaluate the association of various predictive factors with the outcome of surgical repair of urogenital fistula and todetermine the incidence and association of urinary problems post successful fistula repair. Methods: The retrospective analysis was conducted at Maternal Child Health, PIMS, Islamabad. It comprised data related to vesicovaginal fistula repair of patients from January 2008-June 2018. Various modalities were used to determine the underlying cause of these symptoms including patient’s history, examination, ultrasound, urine examination and urodynamic studies. Results: A total of 364 patients of urogenital fistula repair were reviewed, with an overall success in 318 (87.4%) cases.Primary surgical repair of vesicovaginal (90.0%), vesicouterine (86%), ureteric (100%) & ureterovaginal (98%) were more successful. Success rate was further decreased with the history of >1repair attempt of vesicovaginal (71.4%) & vesicouterine (66.5%) fistula. Among 318 successful fistulas repair patients, 78 (24.5%) had urinary problems post operatively. Out of these 78, 56.4% had stress incontinence, 41% infection and 2.6% urge incontinence. Conclusions: Urinary incontinence after fistula repair requires careful evaluation as the successful repair of a urogenital fistula can correct the fistula defect, but it might not make the patient dry.